(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study deals with the heat transfer through helical finned tube. The helical finned tube is taken in order to increase the heat transfer rate. Through the helical finned tube, the heat transfer and entropy generation are evaluated numerically on the basis of constant heat flux and constant wall temperature conditions. In case of constant wall temperature, optimised condition for fin height is obtained. At fin height of 0.002538m the heat transfer is maximum and entropy generation is neither minimum and nor maximum and it lies in between the maximum and minimum value. In case of constant heat flux conditions the entropy generation is continuously decreasing with fin height. Since, the values of heat transfer and entropy generation are calculated for helical finned tube the results obtained are fairly good, as the entropy is not increasing, using helical finned tube we can increase the heat transfer to a larger extent. The report also deals with the heat transfer through external fins, which is used in radiator. The heat transfer and entropy generation of automotive radiator have been numerically evaluated for different fin configurations (louvered, plain, and wavy fin).